Perspectives on delivering health promotion for the intellectual disability population. (23rd June 2022) - Anderson, Joanne; Wickham, Sheelagh
Abstract : The qualitative study reported in this article set out to develop an understanding of how staff supporting individuals with intellectual disabilities deliver health promotion in their practice. The aim was to determine how social care managers working within an intellectual disability care setting in Ireland perceived health promotion and their role within it. Semi-structured interviews were conducted to collect the data. Participants perceived health promotion to be a priority for this population group that should be tailored to meet individual needs. Study participants recognised that they have a role in supporting and providing health promotion for this population, but also that they themselves required more training and education on the issue. Health promotion enablers identified in the study for this client group need to be enhanced and ways to reduce the barriers to access identified. The results reflect observations reported in the literature and indicate a need to prioritise health promotion with this population by establishing policies and practices in the organisation to promote it. A requirement for relevant training and education for social care managers—and other staff, as appropriate—was identified, as were areas for further research.